Microstructural evolution and corrosion behavior of a laser surface modified cast Co–Cr–Mo–C alloy. Issue 8 (3rd July 2020) - Erfanian‐Nazif‐Toosi, Hamid‐Reza; Rodriguez, Mario; López, Hugo F.
Abstract: A Co–Cr–Mo–C biomedical alloy was processed by investment casting, and its surface was modified using pulsed laser melting. The modified surface underwent rapid solidification, and the exhibited microstructure as well as its corrosion properties were investigated. It was found that the laser surface modified (LSM) Co–Cr–Mo–C alloy possesses enhanced corrosion resistance when compared with the same alloy in the as‐cast condition. Microstructural determinations indicated that the LSM Co–Cr–Mo–C alloy exhibited a lack significant solute segregation and a predominantly cellular morphology as a result of the development of a cellular solid–liquid front. The cellular morphology was characterized by a fine distribution of nano‐scale M23 C6 carbides at the intercellular regions. Moreover, the austenite (γ) to athermal ε‐martensite transformation was totally suppressed in the cellular solidified regions. In contrast, the as‐cast alloy develops a coarse dendritic microstructure with coarse carbides in the interdendritic regions. Solute segregation is also present, as well as athermal ε‐martensite (13 pct). It was found that the corrosion resistance of the LSM alloy in the Ringer solution exhibits improved corrosion potential and a reduced corrosion current density (−281 mV and 0.032 μA/cm 2, respectively), when compared with the same alloy in the investment as‐cast condition (−356 mV and 0.150 μA/cm 2 ).